A new low-profile visualized intraluminal support (LVIS) device, LVIS Blue: laboratory comparison between old and new LVIS. (2nd January 2018) - Chung, Joonho; Matsuda, Yoshikazu; Nelson, Jessica; Keigher, Kiffon; Lopes, Demetrius K.
Abstract: Objectives: The Low-profile Visualized Intraluminal Support (LVIS) device is a flexible intracranial stent. The first generation of this system had significant challenges in consistently providing good wall apposition and aneurysm neck coverage. A new modified LVIS, LVIS Blue (Blue), has been developed to address these issues. The purpose of this study is to report a laboratory comparison of wall apposition and aneurysm neck coverage between the original LVIS and Blue. Methods: In bench-top experiments, we noted the visual appearance of the devices and evaluated changes in stent cell angles, neck coverage surface area (%), and stent cell crossing profile for microcatheters using a fusiform aneurysm model. Our in vitro experiments included evaluation of wall apposition and aneurysm neck coverage of the devices under direct radiographic visualization. Results: Blue showed three definite different zones (a mid-zone, a high-density zone, and a transitional zone) and higher metal coverage in the straight fusiform aneurysm model compared to LVIS. Two commercially available microcatheters easily crossed the stent cell at the greater curvature for both devices. In in vitro experiments, Blue showed better wall apposition in tortuous arteries and achieved higher neck coverage in the bifurcation aneurysm compared to LVIS. Discussion: Blue achieved better wall apposition in tortuous arteries and higher aneurysm neck coverage (higher metal-to-artery ratio) in bifurcation aneurysms than LVIS. Our results may provide informative physical properties of LVIS and Blue to be expected when those are used for stent-assisted coil embolization of a large-giant fusiform aneurysm or a bifurcation saccular aneurysm clinically.